2013
DOI: 10.1097/bsd.0b013e3182417103
|View full text |Cite
|
Sign up to set email alerts
|

What is the Optimum Fusion Technique for Adult Isthmic Spondylolisthesis—PLIF or PLF? A Long-Term Prospective Cohort Comparison Study

Abstract: This study strongly supports the use of PLIF to obtain equivalent or superior clinical outcomes compared with PLF for spinal fusion for lumbar IS. Although there are considerable issues when commenting on the results of observational studies, the results of this study are the first to report long-term follow-up beyond 2 years, and further larger long-term randomized studies are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…There are different types of surgical method or techniques that have been developed in past years to achieve fusion and reduction for the deformity of isthmic spondylolisthesis, [5,[41][42][43][44][45][46][47][48][49][50][51][52][53] but it is difficult to define the ideal surgical strategy for IS in adults based on the published data [54][55][56]. Each procedure has its own advantages and disadvantages; the basic principle of surgical treatment is decompression and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of surgical method or techniques that have been developed in past years to achieve fusion and reduction for the deformity of isthmic spondylolisthesis, [5,[41][42][43][44][45][46][47][48][49][50][51][52][53] but it is difficult to define the ideal surgical strategy for IS in adults based on the published data [54][55][56]. Each procedure has its own advantages and disadvantages; the basic principle of surgical treatment is decompression and stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Ekman [20], after 2 year follow up both PLF and PLIF has shown only equal results. In long term cohort study by Cunningham [7], PLIF has shown superior results compared to PLF. In another study by Kee Yong [21] pre op instability is said to play a major role whether addition lumbar interbody fusion would be beneficial or not.…”
Section: Follow Upmentioning
confidence: 97%
“…PLIF had been proved to be superior to PLF in certain studies [6,7,[9][10][11][12][13][14][15][16] whereas certain studies show that PLF is better [8,10,11]. There is a definitive indication to compare both the techniques which is the primary aim of our study.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lumbar and lumbosacral fusion using the pedicle screw system and interbody fusion (IBF) technique is a popular surgical procedure, with satisfactory clinical outcomes and high union rates (7,21,30,33). Since the PLF technique is insufficient for obtaining spinal stability, a number of IBF techniques are developed such as spinous process or iliac wing autografts, allografts, cage, or their combination (10, 11, 20, 21, 34).…”
Section: Yılmaz T Et Al: Modified Technique For Isthmic Spondylolistmentioning
confidence: 99%